GPS Accuracy for Tree Scouting and Other Horticultural Uses - Reza Ehsani; Sherrie Buchanon; Masoud Salyani (EDIS)
Revised! AE438, a 7-page illustrated fact sheet by Reza Ehsani, Sherrie Buchanon, and Masoud Salyani, provides citrus producers using GPS for citrus greening disease scouting with some simple explanations of the causes of GPS error and the level of accuracy that can be expected from different classes of GPS receivers. Published by the UF Department of Agricultural and Biological Engineering, January 2009. Revised October 2009.